L’écologie en milieux populaires : de la débrouillardise à l’action collective - Gaëtan Mangin; Alex Roy (VertigO)
While political measures to encourage sobriety are multiplying, the attention paid to the lifestyles of people in precarious situations is a reminder that ordinary expertise in sobriety has not waited for the crisis to develop and be shared. This expertise is developed on a daily basis through a range of resourceful practices that are economically constrained, but which are also consistent with values firmly rooted in a specific culture. Contrary to the preconceived notion that members of lower classes are ecologically indifferent, can this ordinary expertise be a vector of relations with the environment? Using a survey of not-for-profit organizations and their members, this article explores the contours of a set of ecological practices, discourses and collective initiatives in lower classes environments.